2023
DOI: 10.17977/um065v3i42023p291-302
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Kecerdasan Emosional dan Academic Burnout dengan Prestasi Belajar Siswa SMPN 2 Pakis Kabupaten Malang

Abstract: The purpose of this study was to determine the relationship between emotional intelligence and academic burnout with learning achievement. This study used correlational research design. The total population of class VIII students of SMP Negeri 2 Pakis is 156 students, the sample is 112 students obtained by the slovin formula with a 5 percent allowance. Sampling using simple random sampling method. Data collection used the emotional intelligence scale adapted by Bantolo (2020), and the academic burnout scale "M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In line with this opinion, Syah (2011) divides the factors that influence learning into 3 kinds, namely internal factors (which include the physical and spiritual conditions of learners, external factors (which are the environmental conditions around learners), and learning approach factors (which are the types of learning efforts of learners which include strategies and methods used by learners to carry out activities to study subject matter). Kirana et al (2023) concluded their study as follows: (1) No relationship was found between emotional intelligence and learning achievement in class VIII students of SMP Negeri 2 Pakis, (2) no relationship was found between academic burnout and learning achievement in class VIII students of SMP Negeri 2 Pakis, (3) emotional intelligence and academic burnout together do not have a relationship with the learning achievement of class VIII students of SMP Negeri 2 Pakis because it only has an effect of 2.8% and the rest is influenced by factors outside the study.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this opinion, Syah (2011) divides the factors that influence learning into 3 kinds, namely internal factors (which include the physical and spiritual conditions of learners, external factors (which are the environmental conditions around learners), and learning approach factors (which are the types of learning efforts of learners which include strategies and methods used by learners to carry out activities to study subject matter). Kirana et al (2023) concluded their study as follows: (1) No relationship was found between emotional intelligence and learning achievement in class VIII students of SMP Negeri 2 Pakis, (2) no relationship was found between academic burnout and learning achievement in class VIII students of SMP Negeri 2 Pakis, (3) emotional intelligence and academic burnout together do not have a relationship with the learning achievement of class VIII students of SMP Negeri 2 Pakis because it only has an effect of 2.8% and the rest is influenced by factors outside the study.…”
Section: Introductionmentioning
confidence: 99%